Pemakaian Kosakata Tema Kesehatan dalam Penciptaan Lirik Lagu Anak - Tyasrinestu, Fortunata (Institut Seni Indonesia Yogyakarta, 2021)
The Use of Health-Themed Vocabulary in Creating Children's Song Lyrics. Children's songs can convey the songwriter's messages and describe the children's lives and the environment through their perspective in the lyrics. In this context, the song is the unity of the melody and lyrics. In addition, songs can also function as a means of exploration, information, expression, and entertainment. This research was conducted to determine the description of health-themed vocabulary uses in children's song lyrics. How health vocabulary, especially in children's song lyrics, is used by children's songwriters. The study sample was a set of songs from a collection of the best children's songs, Dendang Kencana. The research used a descriptive-analytical method, which was preceded by a literature study followed by determining the lyrics of the health-themed song lyrics created by the songwriters of Dendang Kencana song album. Data collection was carried out by using the ten-song lyrics with scores. Those songs were the best songs chosen from the Dendang Kencana album. The two songs were the best-selected songs in the Dendang Kencana Children's Songwriting Competition in 2017. The lyrics were observed and recorded, and analyzed to determine the vocabulary used within the children's song lyrics. The vocabulary was then grouped and interpreted according to the purpose of this study. The results show that in children's songs, the vocabulary of the health-themed is often used by the songwriters to emphasize the importance of being healthy and healthy since childhood. The vocabulary is related to children's daily activities, such as bathing, washing hands, washing hair, maintaining a healthy body, exercising, eating nutritiously, and other movement activities.